The Efficacy of Phage Therapy in a Murine Model of Pseudomonas aeruginosa Pneumonia and Sepsis - Yang, Xu; Haque, Anwarul; Matsuzaki, Shigenobu; Matsumoto, Tetsuya; Nakamura, Shigeki (Frontiers in Microbiology, 2021)
The emergence of multi-drug resistant Pseudomonas aeruginosa necessitates the search for treatment options other than antibiotic use. The use of bacteriophages is currently being considered as an alternative to antibiotics for the treatment of bacterial infections. A number of bacteriophages were introduced to treat pneumonia in past reports. However, there are still lack of knowledge regarding the dosages, application time, mechanism and safety of phage therapy against P. aeruginosa pneumonia. We used the bacteriophage KPP10 against P. aeruginosa strain D4-induced pneumonia mouse models and observed their outcomes compared to control models. We found that the nasal inhalation of highly concentrated KPP10 (MOI = 80) significantly improved survival rate in pneumonia models (P < 0.01). The number of viable bacteria in both lungs and in serum were significantly decreased (P < 0.01) in phage-treated mice in comparison to the control mice. Pathological examination showed that phage-treated group had significantly reduced bleeding, inflammatory cell infiltration, and mucus secretion in lung interstitium. We also measured inflammatory cytokine levels in the serum and lung homogenates of mice. In phage-treated models, serum TNFα, IL-1β and IFN-γ levels were significantly lower (P < 0.05, P < 0.01 and P < 0.05, respectively) than those in the control models. In the lung homogenate, the mean IL-1β level in phage-treated models was significantly lower (P <0.05) than that of the control group. We confirmed the presence of phage in blood and lungs, and evaluated the safety of bacteriophage use in living models since bacteriophage mediated bacterial lysis arise concern of endotoxic shock. The study results suggest that phage therapy can potentially be used in treating lung infections caused by Pseudomonas aeruginosa.